Letter to My Daughter. (2nd January 2020) - Liu, Cixin; Field, Jesse
Abstract : International Children's Day, set as June 1, is celebrated in China with school performances, lectures, and guest essays in newspapers and magazines, all on the theme of appreciating the nation's children. "Letter to My Daughter" is acclaimed Chinese science fiction author Liu Cixin's 2013 contribution and has quickly become a classic of the genre.